Polymorphism in a high-entropy alloy - Fei Zhang (Nature Portfolio, 2017)
Whether a polymorphic transition exists in high entropy alloys or not remains unclear since discovery of these alloys more than a decade ago. Here authors report an irreversible polymorphic transition fromfcc to hcp in the prototype FeCoCrMnNi high entropy alloy and provide evidence for fccphase being more stable than hcp phase only at high temperatures.